PEMUJAAN BARONG DI BALI DALAM PANDANGAN ANIMISME EDWARD BURNETT TYLOR - I Putu Ariyasa Darmawan (Sanjiwani: Jurnal Filsafat, 2019)
Edward Burnett Tylor view religion as faith is something spiritual. Religion is not just a theory, memorize, or only an activity, but every religious activity has a spiritual meaning. Edward Burnett Tylor opinion same with Hinduism concept in Bali, that everything all in universe, have a spirit that makes it have such power as man. The worship of Barong in Bali wasn’t worship an object having such a shape an Barong, the entity was created only for ring out God unthinkable to a sort of entity. On the whole, Edward Burnett Tylor opinion emphasize Hindu community confidence in Bali about veneration of Barong, that there is a force the soul a Barong, so that it able to protect people.